Comparative analysis of early adverse events of pelvic organ prolapse repair with or without transvaginal mesh using Clavien‐Dindo classification. Issue 1 (24th April 2018) - Besser, Limor; Schwarzman, Polina; Mastrolia, Salvatore A.; Rotem, Reut; Leron, Elad; Yohay, David; Weintraub, Adi Y.
Abstract: Objective: To assess adverse events following surgical repair of pelvic organ prolapse (POP) with or without the use of transvaginal mesh. Methods: The present retrospective study was conducted among women who underwent surgical POP repair at Soroka University Medical Center, Beer Sheva, Israel, between January 1, 2013, and December 31, 2015. Patients underwent anterior and posterior colporrhaphy either with transvaginal mesh (Elevate Prolapse Repair System; American Medical Systems, Minnetonka, MN, USA) or without transvaginal mesh (native tissue repair). Perioperative adverse events were assessed using the Clavien‐Dindo classification; multivariate regression models were constructed to predict minor and major adverse events. Results: There were 111 women included; 35 were treated with transvaginal mesh, and 76 underwent native tissue repair. Women undergoing native tissue repair had a lower mean grade of cystocele ( P =0.023) and a higher rate of urinary stress incontinence ( P =0.017) than patients treated with transvaginal mesh. The duration of surgery ( P =0.002), duration of hospitalization ( P <0.001), and the amount of blood loss ( P =0.021) were lower in the native tissue repair group. Repair with transvaginal mesh was not associated with increased odds of major or minor adverse events ( P >0.05 for all models examined). Conclusion: Perioperative and postoperative adverse events were comparable regardless of the operative approach. Abstract : Pelvic organ prolapse repair with or without transvaginal mesh demonstrated comparable perioperative and postoperative adverse event rates when using the Clavien‐Dindo classification.